2021
DOI: 10.1128/msphere.00484-21
|View full text |Cite
|
Sign up to set email alerts
|

High Seropositivity Rate of Neutralizing Antibodies to Astrovirus VA1 in Human Populations

Abstract: Astroviruses are human pathogens with emerging disease associations, including the recent recognition of their capacity to cause meningoencephalitis. Astrovirus VA1 is the most commonly identified astrovirus genotype from cases of human encephalitis, but it is unknown what percentage of the human population has neutralizing antibodies to VA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…A previously described fluorescent focus forming assay (FFA) was used to quantify the infectious titer of VA1 in focus forming units per mL (FFU/mL). Caco-2 cells were seeded into 96- well plates 38 . Multi-step growth curves were completed using Caco-2 cells with samples collected at 1, 24, 48, and 96 hpi.…”
Section: Methodsmentioning
confidence: 99%
“…A previously described fluorescent focus forming assay (FFA) was used to quantify the infectious titer of VA1 in focus forming units per mL (FFU/mL). Caco-2 cells were seeded into 96- well plates 38 . Multi-step growth curves were completed using Caco-2 cells with samples collected at 1, 24, 48, and 96 hpi.…”
Section: Methodsmentioning
confidence: 99%
“…Tus, our results suggest that the observed mutations in the capsid protein do not have the capacity to cause signifcant antigenic variation. Serological assays using the neutralization of the virus as a quantitative measurement of antibodies have been used to evaluate the extent of AstV infection among human and animal populations [32,33]. However, the poor growth of avian AstVs in cell culture has hampered the widespread use of this assay to test feld sera.…”
Section: Discussionmentioning
confidence: 99%
“…The cell membrane was then permeabilized with 0.2% Triton X-100 (Sigma) in PBS for 15 min at room temperature. Next, samples were immunostained using a monoclonal neutralizing antibody (2A2, ref (5)), followed by incubation with protein A coupled to peroxidase. Finally, the cells were washed twice with PBS and stained with 50 μl of a solution containing 1 mg/ml of 3-amino-9-ethyl carbazole (AEC), 0.04% H 2 O 2 , and sodium acetate buffer (50 mM, pH 5).…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly associated astrovirus genotype in human neurological disease is VA1. A recent report on the seroprevalence of neutralizing antibodies from two cohorts of adult and pediatric serum samples found the seropositivity rate in adults to be approximately 77%, and it was concluded that a majority of humans are exposed to VA1 between 2 and 9 years of age (5).…”
Section: Introductionmentioning
confidence: 99%